The evolution of design with concerns on sustainability - Vicente, J.A. (2016)
This paper aims to analyse the birth and evolution of design with concerns over sustainability, in the context of social and civilizational changes experienced since the industrial revolution, with particular focus since the post-war period and in the context of sustainable development. It will examine several factors that influenced this design approach and that drove its evolution through different stages of maturity and complexity. It will analyse the various forms of design with environmental concerns, as well as the inclusion of other criteria in the context of sustainability, namely social ones. The aim is to settle knowledge that can allow us to draw some lessons to meet the challenges we face today.